Chemometrics Application for Grouping and Determinating Volatile Compound which related to Antioxidant Activity of Turmeric Essential Oil (Curcuma longa L) - Rosy Islamadina; Adelin Can; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2020)
Turmeric essential oil is known to have antioxidant activity. Various in vitro antioxidantactivity assays has been carried out. Related to this research, it tries to examine the antioxidantpotential of turmeric essential oil and see the composition that is responsible for antioxidant activitycombine with chemometrics. The research method used was a narrative review of 60 articlesobtained from several databases. The review conducted on profiling essential oil compounds thatidentified using GC-MS and evaluation of the antioxidant activity of turmeric essential oil with themost commonly used method including scavenging radical 2,2 diphenyl-1-picrylhydrazyl (DPPH)and 2,2-azinobis (3-ethylbenzothiazoline-6 sulfonic acid (ABTS). Analysis methods used forgrouping various multivariate data subjects and determaining the relationship between thevariables were Principal Component Analysis (PCA) and Cluster Analysis (CA). According to thereview, turmeric essential oils are proven to have potential antioxidant activity and have variationsin chemical contents. PCA was success for grouping subjects with various correlated variables,determining variables wich the most influential and correlation between variables. CA method canbe used to group samples without requiring mutually correlated variables.